Novel Materials From the Supramolecular Self-Assembly of Short Helical β3-Peptide Foldamers - Kulkarni, Ketav; Habila, Nathan; Del Borgo, Mark P.; Aguilar, Marie-Isabel (Frontiers in Chemistry, 2019)
Self-assembly is the spontaneous organisation of small components into higher-order structures facilitated by the collective balance of non-covalent interactions. Peptide-based self-assembly systems exploit the ability of peptides to adopt distinct secondary structures and have been used to produce a range of well-defined nanostructures, such as nanotubes, nanofibres, nanoribbons, nanospheres, nanotapes and nanorods. While most of these systems involve self-assembly of α-peptides, more recently β-peptides have also been reported to undergo supramolecular self-assembly which have been used to produce materials, such as hydrogels, that are tailored for applications in tissue engineering, cell culture and drug delivery. This review provides an overview of self-assembled peptide nanostructures obtained via the supramolecular self-assembly of short β-peptide foldamers with a specific focus on N-acetyl-β3-peptides and their applications as bio- and nanomaterials.